1988
DOI: 10.1111/j.1365-2621.1988.tb08978.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Free Radicals in Beer Oxidation

Abstract: ReagentsShort-lived radicals produced during the incubation of beer at 60°C were detected by electron spin resonance (ESR) spectroscopic analysis using N-teti-butyl-cY-phenylnitrone (PBN) as a spin trapping reagent. The hyperfine splitting (hfs) constants were 15.7 f 0.2 G and 3.2 t 0.2 G for 01~ and a!, respectively. The hfs constants of PBN adducts produced by Coho y irradiation were 15.6 rf: 0.3 G and 3.1 -C 0.2 G for on and CY~ in beer and 15.7 f 0.3 G and 3.3 of: 0.3 G for on and c$r in double distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…The oxidation of flavour compounds in wort and/or beer is initiated by the reaction of oxygen with transition metals, such as iron and copper, thus generating the superoxide anion (), which may be further reduced and protonated to hydrogen peroxide (H 2 O 2 ). The superoxide anion and hydrogen peroxide can then undergo the Haber–Weiss and Fenton reactions, respectively, with iron and/or copper ions to produce the very reactive hydroxyl radical (OH ˙ ) (Kaneda et al. 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of flavour compounds in wort and/or beer is initiated by the reaction of oxygen with transition metals, such as iron and copper, thus generating the superoxide anion (), which may be further reduced and protonated to hydrogen peroxide (H 2 O 2 ). The superoxide anion and hydrogen peroxide can then undergo the Haber–Weiss and Fenton reactions, respectively, with iron and/or copper ions to produce the very reactive hydroxyl radical (OH ˙ ) (Kaneda et al. 1988).…”
Section: Introductionmentioning
confidence: 99%
“…As cited in the Introduction, it has been shown that active oxygens such as superoxide (02-), hydrogen peroxide (HzOz), and the hydroxyl radical ('OH) are produced during the process of beer oxidation (Kaneda et al, 1988(Kaneda et al, , 1989(Kaneda et al, ,1990(Kaneda et al, ,1991. The active oxygens attack several beer components and initiate a series of free-radical reactions, leading to beer staling.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it can be expected that a beer with a longer ESR lag time will be more flavour stable than a beer with a shorter ESR lag time. Furthermore, the specificity and intensity of the ESR signal after 150 minutes of forced aging at 60°C was reported to give an indication of the intensity of the aged character, the extent of the oxidative processes and the rate of radical formation after exhaustion of the antioxidant potential and the onset of beer staling 10,11,29 . An example of a typical ESR graph for a "standard" rated beer and for a "reject" rated beer is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…ESR is now widely used to detect ROS in the context of beer aging. Although a number of beer radicals are presumed to be involved in flavour staling, only one reactive oxygen species -the 1-hydroxyethyl radical is probably directly measured by ESR 1,10,11,29 . Developments like those above will extend the usefulness of this approach 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation